The Impact of General Elections in India on Stock Markets and Investors’ Behavioural Biases in the Medium and Short Term - Singhania, Arun (Digital Repository of Theses, 2025)
Preliminary observations from historical data of the Indian stock market during the five Indian General Elections (GEs)—specifically in 2004, 2009, 2014, 2019, and 2024—reveal predictable and anomalous market behaviour patterns. Firstly, an examination of medium-term performance revealed that the total stock market returns, as reflected by the NIFTY50 Total Return Index (NIFTRI), experienced an impressive average growth of 35.1% across the five election years. When considering individual election years, the returns ranged from 14.16% to 77.8% annually. The substantial average growth notably exceeds the historical long-term average annual return of 14.92% observed during non-election years from 2000 to 2024. Secondly, evidence from market data of a shorter timeframe—approximately one month surrounding the announcement of GE results—revealed that the India VIX, which measures market volatility, demonstrated unusually heightened volatility compared to non-election periods over the 16-year period from 2008 to 2024. These findings suggest a departure from the principles outlined in the Efficient Market Hypothesis (EMH), a cornerstone of traditional finance. According to the EMH, investors are presumed to be rational actors who instantly incorporate all pertinent information into stock prices, rendering the market unpredictable. Conversely, this study posits that investor behaviour during GEs is markedly influenced by psychological factors distinct in “Behavioural Finance” theories. Such biases undermine intrinsic market valuations, leading to discrepancies between investor preferences and probabilities derived from classical financial theories. Appropriate statistical tests conducted with the empirical data presented herein established that significant differences in returns and volatility exist within the Indian stock markets during Indian GEs, as opposed to other periods. Furthermore, the survey methodology employed in this research confirmed the prevalence of significant cognitive and emotional biases among investors. This elucidation provides insight into the underlying financial biases that contribute to predictable price movements and heightened volatility in the market during times of economic uncertainty. The study emphasises that investors and policymakers must acknowledge these biases and adopt informed investment strategies during uncertain times to mitigate potential losses. Ultimately, it makes a substantial contribution to the field of “Behavioural Finance,” reinforcing its principles and expanding its theoretical frameworks across diverse contexts, conditions, and timeframes. Keywords: Indian General Elections, Stock Market Volatility and Returns, Efficient Market Hypothesis, Behavioural Finance, Cognitive and Emotional Biases.